PENGERINGAN BELIMBING WULUH (AVERRHOA BILIMBI L) MENGGUNAKAN TIPE LORONG BERBASIS ARDUINO MEGA 2560 - Iskandar; Syahputra Karo-karo, Riduan; Abdul Rachman, Nazaruddin (JURUTERA - Jurnal Umum Teknik Terapan, 2024)
Starfruit (Averrhoa Bilimbi L) is a starfruit vegetable that is often used by Indonesian people as an acid in kitchen spices. Starfruit (Averrhoa Bilimbi L) is often made into suntan acid so that it can be used for 1-1.5 years because it has undergone a drying process. The drying process for Starfruit (Averrhoa Bilimbi L) is still traditional, namely by drying it in direct sunlight. This drying is less efficient because it is influenced by several factors such as weather factors and the length of the drying process which can affect the quality and color of sunti acid. This research aims to find out how to design and design tools, as well as time and temperature in processing the tunnel type Starfruit (Averrhoa Bilimbi L) using a blower system with heat control based on Arduino Mega 2560. The research method used in this research is quantitative research. The research results show that the design and design in this research have been successfully designed, overall, this tool is shaped like a tube with several supporting components, namely LPG gas, blower, and drum holder. The time needed to reach a dry Belimbing Wuluh is done in 6 stages with an interval of 120 minutes, so the total is 12 hours. The temperatures that occur in both T1, T2, and T3 vary as seen from the test graph. Temperature testing in this test uses a MAX6675 sensor with a thermocouple connected to an Arduino Mega 2560. To measure weight, use a manual scale. It is recommended that the drying room be made denser so that it can produce good heat. The addition of a blower is very necessary so that the hot air can be distributed thoroughly. It is hoped that this starfruit dryer can be developed even better and can help the community in drying wealth starfruit.